(untitled) - Watkinson, Anne (London, 2008)
This indispensable textbook provides the underpinning knowledge to support all Teaching Assistants working towards Level 3 of the National Occupational Standards.
Keywords: Teachers’ assistants,Teachers’ assistants,Trợ lý giáo viên,Trợ lý giáo viên; Certification,Giấy chứng nhận; Great Britain,Great Britain,Nước Anh,Nước Anh